A Study on Finite Element Modelling and Analysis with respect to Experimental Results of Strengthened Unreinforced Masonry Walls With and Without Kevlar-FRP - Sugeng Wijanto; Takim Andriono; Jovita Tanudjaja (Civil Engineering Dimension, 2021)
Unreinforced masonry (URM) walls, found in most historical buildings in Indonesia, are relatively brittle with wide variety of material properties. The behaviour of URM walls is very complex, especially when subjected to seismic excitation. In this research, a finite element modelling was set up in order to analyse the seismic performance of URM wall experimental test units, with and without strengthening material. The analysis was conducted using SAP2000 computer program. Three dimensional solids and springs as link connectors were assigned to represent the masonry behaviour. This research aims to compare results obtained from the computer analysis and the previously conducted laboratory experiments. The effectiveness of Kevlar fibre material, which was installed on both wall surfaces and modelled as truss element was also investigated. It was found that the failure mechanisms shown by the SAP2000 model was similar to the laboratory test results. The use of Kevlar Fibre as strengthening material was found able to significantly increase the stiffness and shear capacity of the URM wall.